Prognostic Analysis and Comparison of the 2014 and 2018 International Federation of Gynecology and Obstetrics Staging System on Overall Survival in Patients with Stage IIB-IVA Cervix Carcinoma - Song T; Xu H; Shi L; Yan S (Dove Medical Press, 2022)
Tao Song,1,2 Hong'en Xu,2 Lei Shi,2 Senxiang Yan1 1Department of Radiation Oncology, The First Affiliated Hospital, Zhejiang University School of Medicine, Hangzhou, 310003, Zhejiang, People's Republic of China; 2Cancer Center, Department of Radiation Oncology, Zhejiang Provincial People's Hospital, Affiliated People's Hospital, Hangzhou Medical College, Hangzhou, Zhejiang, 310014, People's Republic of ChinaCorrespondence: Senxiang Yan, Department of Radiation Oncology, The First Affiliated Hospital, Zhejiang University School of Medicine, No. 79, Qingchun Road, Shangcheng District, Hangzhou, 310003, People's Republic of China, Tel +86 571-87236403, Email yansenxiang@zju.edu.cnPurpose: This study aimed to assess the prognostic factors of overall survival (OS) in patients with stage IIB-IVA cervix carcinoma (CC) who underwent external beam radiation therapy (EBRT) and brachytherapy (BRT) and to compare the prognostic accuracy of the 2014 and 2018 International Federation of Gynecology and Obstetrics (FIGO) staging system using the Surveillance, Epidemiology, and End Results (SEER) database.Methods: Patients with a histopathological diagnosis of CC between 2004 and 2016 were included. The primary endpoint was OS. The prognostic significance for OS was analyzed by the Cox regression model. Prognostic accuracy in evaluating 3- and 5-year OS in different staging systems was evaluated using time-dependent receiver operating characteristic (tdROC) curves.Results: A total of 2585 patients with stage IIB-IVA CC, staged according to the 2014 FIGO staging system, were included in the study. The 3- and 5-year OS rates were 63.9% and 56.6%, respectively, with a median OS of 98 months. Independent variables, such as older age at diagnosis, histological grades apart from well or moderately differentiated, large tumor size, advanced tumor stages classified according to the 2014 and 2018 FIGO staging systems and treatment without chemotherapy or unknown were associated with a worse OS. A tdROC analysis conducted using DeLong's tests revealed no significant difference in the prediction of 3- and 5-year OS between the 2014 and 2018 FIGO staging systems (P = 0.912 and 0.863, respectively).Conclusion: Both 2014 and 2018 FIGO staging systems were strong prognostic factors for OS. No significant risk classification was observed for stage IIIC1 disease in the revised 2018 FIGO staging system for patients who underwent EBRT and BRT.Keywords: prognostic analysis, Surveillance, Epidemiology, and End Results database, staging, survival, risk factors